2004
DOI: 10.1111/j.0022-202x.2004.23444.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Characterization of Loss of Function Mutations of the Human Melanocortin 1 Receptor That Are Associated with Red Hair

Abstract: Variation in skin color is the major host risk factor for melanoma and other forms of skin cancer. Individuals with red hair show an increased ratio of phaeomelanin to eumelanin in both hair and skin. This ratio is regulated by the melanocortin (MC) 1 receptor. There are several common point mutations in the human MC1 receptor that are overrepresented in North European red-heads, and in individuals with pale skin. In order to determine the functional significance of these mutations, we expressed the Asp84Glu, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
90
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(108 citation statements)
references
References 30 publications
11
90
0
2
Order By: Relevance
“…It is more plausible that the decrease in basal activity reflects a polymorphism-induced transition to a less active receptor state with an accompanying decrease in agonist potency as predicted by the extended ternary model (Lefkowitz et al, 1993). The V60L and R163Q polymorphisms displayed agonist potency and affinity similar to the wild-type receptor, consistent with previous reports (Schiöth et al, 1995;Ringholm et al, 2004;Beaumont et al, 2005Beaumont et al, , 2007.…”
Section: Downloaded Fromsupporting
confidence: 87%
“…It is more plausible that the decrease in basal activity reflects a polymorphism-induced transition to a less active receptor state with an accompanying decrease in agonist potency as predicted by the extended ternary model (Lefkowitz et al, 1993). The V60L and R163Q polymorphisms displayed agonist potency and affinity similar to the wild-type receptor, consistent with previous reports (Schiöth et al, 1995;Ringholm et al, 2004;Beaumont et al, 2005Beaumont et al, , 2007.…”
Section: Downloaded Fromsupporting
confidence: 87%
“…The R163Q variant in earlier studies was associated with lower affinity for a-MSH but normal level of cAMP response than wild type MC1R. 31 However, more recent studies have associated this variant with decreased surface expression, reduced affinity for a-MSH as well as cAMP signaling but to a lower extent than the RHC alleles. 30,33 Nonpigmentary functions of MC1R include regulation of cytokines and their receptors involved in immune and inflammatory responses through modulation of NF-jB.…”
Section: Discussionmentioning
confidence: 93%
“…MC1R preferentially binds the pro-opiomelanocortin-derived peptides ␣-melanocyte-stimulating hormone (␣-MSH) and adrenocorticotropic hormone, which leads to an elevation in intracellular cAMP levels (10). RHC variant MC1Rs have been demonstrated to elicit weak cAMP responses as a result of reduced receptor coupling (2,(11)(12)(13) or abnormal receptor localization (2,(12)(13)(14)(15). Molecular analysis has revealed that MC1R signaling modulates the expression and function of the microphthalmia-associated transcription factor, a key regulator of pigmentation genes, suggesting that this pathway underlies MC1R coordination of melanogenesis (16).…”
mentioning
confidence: 99%